2021
DOI: 10.3390/molecules26113134
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profile, Antioxidant Capacity, α-Amylase and α-Glucosidase Inhibitory Potential of Wild Moroccan Inula viscosa (L.) Aiton Leaves

Abstract: Medicinal plants offer imperative sources of innovative chemical substances with important potential therapeutic effects. Among them, the members of the genus Inula have been widely used in traditional medicine for the treatment of several diseases. The present study investigated the antioxidant (DPPH, ABTS and FRAP assays) and the in vitro anti-hyperglycemic potential of aerial parts of Inula viscosa (L.) Aiton (I. viscosa) extracts through the inhibition of digestive enzymes (α-amylase and α-glucosidase), re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 57 publications
(71 reference statements)
0
25
0
Order By: Relevance
“…Diphenyl-1-picrylhydrazyl (DPPH) assay was conducted to determine the radical scavenging activity of the different extracts as adopted by Hatano et al 53 with some modifications suggested by Asraoui et al 54 . For this purpose, 50 µL of plants extracts at different concentrations were mixed with 150 µL of 0.004% freshly prepared methanol solution of DPPH in a 96-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…Diphenyl-1-picrylhydrazyl (DPPH) assay was conducted to determine the radical scavenging activity of the different extracts as adopted by Hatano et al 53 with some modifications suggested by Asraoui et al 54 . For this purpose, 50 µL of plants extracts at different concentrations were mixed with 150 µL of 0.004% freshly prepared methanol solution of DPPH in a 96-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…Few studies reported the inhibitory activity of D. viscosa on α-amylase and α-glucosidase. Asraoui et al [ 7 ] showed that the D. viscosa leaves have an important inhibitory effect against α-glucosidase with an IC 50 of 0.0653 mg/mL and an inhibitory effect against α-amylase of 27% at 1 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…HPLC-DAD-ESI/MS analysis of polyphenolic compounds from the methanolic extract of D. viscosa was conducted on a liquid chromatography system (Shimadzu, Kyoto, Japan). The same protocol of separation and quantification has already been published in the work of Asraoui et al [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations